Design and Implementation of a Raspberry Pi-Based Laser Harp - Liu, Ziang (International Journal of Computer Science and Information Technology, 2026)
This report shows how the laser harp was built step by step. First, it gives a brief introduction of the STEM background in the UK and lists out the key issues in engineering. Then it presents the aim of attracting young pupils to study engineering and lists the objectives of the laser harp project. Secondly, previous work, including two styles of laser harp and designs related to laser harp is carefully reviewed and analyzed. Thirdly, the design of the harp in this project, which uses button circuits, a Raspberry Pi-based system structure as the hardware, and Python and Sonic Pi based programmes as software, is shown. Fourthly, the results are presented and discussed, and then the challenges encountered during the project are analyzed. Finally, a conclusion is provided, summarising how the laser harp achieves the aims and most objectives and then points out possible improvements for the future.